Enhancing the bearing capacity of rigid footing using limited life kenaf geotextile reinforcement - Shirazi, Mohammad Gharehzadeh; A Rashid, Ahmad Safuan; Nazir, Ramli; Abdul Rashid, Azrin Hani; Horpibulsuk, Suksun (Taylor and Francis Ltd., 2020)
This research focuses on soft clay improvement by using Kenaf textile as a natural geotextile reinforcement. A series of small-scale laboratory tests were conducted to study the impact of the geotextile reinforcement depth, d, the vertical spacing between reinforcement, S and the number of reinfor- cement layers, N on the bearing capacity of the soil model. The test results were verified using the numerical simulation by PLAXIS 2D. In this study, the influence factors included four different d/B ratios of 0.25, 0.5, 0.75 and 1.0; three different S/B ratios of 0.25, 0.5 and 0.75, and a different number of reinforcement layers, N from 1 to 4 were investigated where B is the footing width. The results clearly showed that the bearing capacity of rigid footings was significantly improved with the Kenaf geotextile layers in the kaolin. The measured and predicted bearing capacity results were in good agreement. The optimum d/B ratio and S/B ratio, which resulted in the maximum ultimate bearing capacity of the Kenaf-reinforced model ground were about 0.25 and 0.25, respectively. The optimum N was 3, i.e., the bearing capacity insignificantly improved even with N > 3.